Konsep Dinasti dalam Pembentukan Optima dalam Hukum Positif Indonesia dan Hukum Perdata Islam: Konsep Dinasti dalam Pembentukan Optima dalam Hukum Positif Indonesia dan Hukum Perdata Islam - Taufik Hidayat; Dayang Rafidah binti Syariff M. Fuad; wahyudi (Dame Journal of Law, 2025)
This article examines the concept of Dinasti in Optima Forma from the perspectives of Indonesian positive law and Islamic civil law. The term "dynasty" in political and legal contexts is often understood as a hereditary transmission of power. Meanwhile, the Latin phrase in optima forma implies an ideal or most perfect form of a system. This study aims to evaluate whether a dynastic system in its ideal form can be accepted and institutionalized within national and Islamic legal frameworks, or whether it contradicts the principles of justice, meritocracy, and public welfare. The research employs a normative and comparative legal approach. The findings reveal both convergences and conceptual divergences between the two legal systems in assessing the legitimacy and validity of dynastic power structures.